Dynamic Response Analysis of Ballastless Tracks Considering the Temperature-Dependent Viscoelasticity of Cement-Emulsified Asphalt Mortar Based on a Vehicle–Track–Subgrade Coupled Model - Yunqing Chen; Bing Wu; Linquan Yao; Xianglong Su (Lubricants)
This study aims to explore the dynamic response of ballastless tracks under various temperatures of the cement-emulsified asphalt (CA) mortar layer and other environmental factors. CA mortar is the key material in the ballastless track structure, exhibiting notably temperature-dependent viscoelastic properties. It can be damaged or even fail due to the continuous loads from trains. However, the dynamic behaviors of ballastless tracks considering the temperature-dependent viscoelasticity of CA mortar have been insufficiently studied. This paper captures the temperature-dependent viscoelastic characteristics of CA mortar by employing the fractional Maxwell model and applying it to finite element simulations through a Prony series. A vehicle–track–subgrade (VTS) coupled CRTS I ballastless track model, encompassing Hertz nonlinear contact and track irregularity, is established. The model is constrained symmetrically on both of the longitudinal sides, and the bottom is fixed on the infinite element boundary, which can reduce the effects of reflected waves. After the simulation outcomes in this study are validated, variations in the dynamic responses under different environmental factors are analyzed, offering a theoretical foundation for maintaining the ballastless tracks. The results show that the responses in the track subsystem will undergo significant changes as the temperature rises; a notable effect is caused by the increase in speed and fastener stiffness on the entire system; the CA mortar layer experiences the maximum stress at its edge, which makes it highly susceptible to damage in this area. The original contribution of this work is the establishment of a temperature-dependent vehicle–track–subgrade coupled model that incorporates the viscoelasticity of the CA mortar, enabling the investigation of dynamic responses in ballastless tracks.